Development of Digital Literacy Tools in the Implementation of Science, Technology, Engineering, Art, and Mathematics (STEAM) Learning for the Implementation of the Independent Curriculum for Children Aged 5-6 Years - Hafizzaturroyani, Hafizzaturroyani; Habibi, Muazzar; Fahruddin, Fahruddin; Darmiany, Darmiany; Subarinah, Sri (International Journal of Education and Digital Learning (IJEDL), 2024)
This research aims to describe the development of digital literacy tools in the implementation of science, technology, engineering, art and mathematics (STEAM) learning for the implementation of the Independent Curriculum. The type of research used in this research is development (Development research) which aims to produce a product. The development research procedure used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data collection technique used in this research is a non-test instrument consisting of instrument validation sheets, feasibility sheets, effectiveness and usability of devices, interview sheets, observation sheets. Data analysis techniques are used to determine the feasibility, usefulness, and effectiveness of digital literacy tools. The research results of the digital literacy tools developed are very valid and reliable, so they are suitable for use in STEAM learning for implementing the independent curriculum for children aged 5-6 years. The digital literacy tools in STEAM learning that were developed are effective for use with children aged 5-6 years in the very high category. The digital literacy tools in STEAM learning that were developed are included in the very practical category based on the learning implementation observation sheet and teacher questionnaire.